Socioeconomic Inequality in Israel A Theoretical and Empirical Analysis - Khattab, Nabil; Miaari, Sami.; Stier, Haya.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This volume addresses different aspects and areas of inequality in Israel, a country characterized by high levels of economic inequality, poverty, and social diversity. The book expands on the mechanisms that produce and maintain inequality, and the role of state policies in influencing those mechanisms.
Keywords: Science; Science; Science, general; Electronic books